The multimodal organization of feedback and its documentation: multiactivity during formal, formative reading assessment - Tomasine, Joseph S. (Frontiers in Communication, 2024)
This multimodal conversation analytic study draws upon naturally-occurring data from formal, formative reading assessment in an elementary school, general education classroom to investigate the interactional practice of documenting feedback. This consists of the ways teachers and students engage in both oral feedback and its written documentation simultaneously during interaction. Such competencies have been underappreciated by educational research on assessment literacies. Moreover, prior interactional research on formal formative assessment has shed light on talk-based practices that enable oral feedback but have nonetheless neglected the embodied and material practices that are necessary for its written documentation. To investigate how talk, embodiment and materiality enable feedback to be documented within multiactivity, the current study collected instances of the practice from a multimodal corpus of audio-visual recordings and electronic scans of completed assessment materials. Examination of this collection uncovered straightforward, problematic and complex interactional trajectories as well as their relationships to institutional outcomes. The study concluded that the more participants to formal, formative reading assessment focus on feedback as talk-in-interaction, the less explicitly that talk-in-interaction is represented in the written documents they collaboratively produce. As a result, important details of both teacher interventions and student performances may be rendered opaque in the material record of the assessment events. These findings extend a burgeoning multimodal turn in the interactional analysis of formal formative assessment and aim to provoke subsequent educational research into interactional assessment literacies.